Atg9 Cycles between Mitochondria and the Pre-Autophagosomal Structure in Yeasts - Reggiori, Fulvio (2005)
Autophagy is a degradative process conserved among eukaryotic cells. It allows the elimination of cytoplasm including aberrant protein aggregates and damaged organelles. Accordingly, it is implicated in normal developmental processes and also serves a protective role in tumor suppression and elimination of invading pathogens, whereas defects in autophagy are associated with various human diseases including cancer and neurodegeneration. Atg proteins mediate the sequestration event that occurs at the preautophagosomal structure (PAS) by catalyzing the formation of double-membrane vesicles, termed autophagosomes. In Saccharomyces cerevisiae, the integral membrane protein Atg9 that is required for autophagy cycles through the PAS. Here, we demonstrate that Atg9 shuttles between this location and mitochondria. These data support a new model where mitochondria may provide at least part of the autophagosomal lipids and suggest a novel cellular function for this well-studied organelle.